Study on the impact of digital countryside construction on fostering sports industry development: based on the moderating role of market-oriented factor allocation and the mediating role of rural consumption upgrade - Zhang, Xinxin; Wang, Sen; Li, Tianpei; Sun, Shuangcheng (Frontiers in Artificial Intelligence, 2025)
IntroductionAgainst the backdrop of China’s coordinated advancement of the “Digital China” and “Rural Revitalization” development strategies, digital countryside construction has emerged as a new opportunity for the sports industry.MethodsBased on panel data from 21 provinces in China from 2015 to 2023, this study employs fixed-panel models, moderation effects models, and mediation effects models to examine the relationship between digital countryside construction and the sports industry, as well as its underlying mechanisms.ResultsDigital countryside construction exerts a significant positive promotion on the sports industry; Market-oriented factor allocation exerts a significant positive moderating influence on the impact of digital countryside construction on the sports industry; Rural consumption upgrade plays a significant positive mediating role in the influence of digital countryside construction on the sports industry. In terms of regional heterogeneity, the eastern region exhibits a significant promoting effect, while the central region shows a suppressing effect that is not statistically significant. The western region also demonstrates a promoting effect, though it is not statistically significant.DiscussionImplementing region-specific development strategies, tailored to local conditions, is of paramount significance for achieving the maximal policy benefits of digital countryside construction. This should be accomplished by deepening market-oriented reforms and enhancing digital infrastructure to foster balanced and high-quality development of the sports industry in both urban and rural areas.